Analysis of Caputo Impulsive Fractional Order Differential Equations with Applications. (13th February 2013) - Mahto, Lakshman; Abbas, Syed; Favini, Angelo
Abstract : We use Sadovskii's fixed point method to investigate the existence and uniqueness of solutions of Caputo impulsive fractional differential equations of orderα ∈ ( 0, 1 ) with one example of impulsive logistic model and few other examples as well. We also discuss Caputo impulsive fractional differential equations with finite delay. The results proven are new and compliment the existing one.